2019
DOI: 10.3389/fchem.2019.00462
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Wells-Dawson Clusters Associated With the Small Ribosomal Subunit

Abstract: The polyoxometalate P 2 W 18 , the Wells-Dawson cluster, stabilized the ribosome sufficiently for the crystallographers to solve the phase problem and improve the structural resolution. In the following we characterize the interaction of the Wells-Dawson cluster with the ribosome small subunit. There are 14 different P 2 W 18 clusters interacting with the ribosome, and the types of interactions range from one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
(234 reference statements)
0
5
0
Order By: Relevance
“…Moreover, POMs have shown pharmacological activities in vitro and in vivo, such as antitumor, antimicrobial, and antidiabetic [2,3]. Their roles in biological systems are non-functional or functional kind of interactions with biomolecules [4], like the tungstate cluster that helps to solve the X-ray structure of ribosome [5] or the insulin-like properties of the decavanadates [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, POMs have shown pharmacological activities in vitro and in vivo, such as antitumor, antimicrobial, and antidiabetic [2,3]. Their roles in biological systems are non-functional or functional kind of interactions with biomolecules [4], like the tungstate cluster that helps to solve the X-ray structure of ribosome [5] or the insulin-like properties of the decavanadates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganics 2020, 8, x FOR PEER REVIEW 2 of 20 the tungstate cluster that helps to solve the X-ray structure of ribosome [5] or the insulin-like properties of the decavanadates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tedeschi and Harris have convincingly shown that the permeability of the mitochondrial membrane also follows these patterns. Biological membranes are characterized by very high electrical resistance and capacitance; this implies the presence of structures containing a continuous dielectric layer, which can be created by a continuous lipid phase [29]. Pauli has recently established that the mitochondrial membrane is also characterized by high electrical resistance.…”
Section: Membrane Ultrastructurementioning
confidence: 99%
“…Additionally, the favorable binding of POMs to protein surfaces renders them ideally suited for facilitating the crystallization of proteins and solving their structures through X‐ray diffraction [15–17] . The most prominent example of this is perhaps the important dual role of POMs in generating phases and inducing post‐crystallization rearrangements that allowed the structure of the ribosome to be solved, for which the 2009 Nobel Prize in Chemistry was awarded [15–18] …”
Section: Introductionmentioning
confidence: 99%